Konsep Muzhaharah Terhadap Pemimpin Dalam Perspektif Hukum Tata Negara Dan Hadits Nabi Saw - Nur Zaqia (JOURNAL OF ISLAMIC AND LAW STUDIES, 2018)
ABSTRACTThe emergence of community actions especially students as a response to the socio-political conditions in a country for policies that are not pro-people, raises the problem of understanding these actions. The formulation of the problem in this research is how the history of demonstrations in the perspective of Islam and how the law demonstrates leaders who are not trustworthy in the perspective of hadith. This type of research is a literature study. The research results obtained that the concept of muzhaharah against leaders who are not trustworthy in the perspective of Constitutional Law is legal but is expected not to be accompanied by vandalism or anarchism that is with polite and wise language without opening disgrace and blaspheming the authorities . ABSTRAKMunculnya tindakan-tindakan masyarakat khususnya Mahasiswa sebagai respon terhadap kondisi sosial politik di sebuah negara atas kebijakan-kebijakan yang tidak pro rakyat, menimbulkan problematika pemahaman atas tindakan-tindakan tersebut. Rumusan masalah dalam penelitian ini adalah bagaimana sejarah demonstrasi dalam perspektif islam dan bagaimana hukum mendemo pemimpin yang tidak amanah dalam perspektif hadis. Jenis penelitian ini adalah penelitian studi pustaka.Hasil penelitian diperoleh bahwa konsep muzhaharah terhadap pemimpin yang tidak amanah dalam perspektif Hukum Tata negara ialah sah-sah saja namun diharapkan tidak disertai dengan perusakan atau anarkisme yaitu dengan bahasa yang santun dan bijak tanpa membuka aib dan menghujat penguasa .